Optimized UV-Spectrophotometric Assay to Screen Bacterial Uricase Activity Using Whole Cell Suspension - Pugin, Benoit; Plüss, Serafina; Mujezinovic, Denisa; Nielsen, Rikke C.; Lacroix, Christophe (Frontiers in Microbiology, 2022)
Uricase catalyzes the conversion of uric acid into allantoin with concomitant reduction of molecular oxygen to hydrogen peroxide. In humans, uricase is not functional, thereby predisposing individuals to hyperuricemia, a metabolic disturbance associated with gout, chronic kidney disorders and cardiovascular diseases. The efficacy of current therapies to treat hyperuricemia is limited, and novel approaches are therefore desired, for instance using uricase-expressing probiotic strains. Here we evaluated UV-spectrophotometric and H2O2-based fluorescent assays to enable the rapid identification of uricase activity in a broad panel of lactobacilli, Bacillus, and Bifidobacterium species. We highlighted abiotic (medium composition and mode of sterilization) and biotic (H2O2-producing strains) factors impacting the measurements’ accuracy, and reported on the stepwise optimization of a simple, fast, and robust high-throughput UV-spectrophotometric method to screen uricase activity using whole bacterial suspension, thereby assessing both cell-associated and extracellular activity. The validity of the optimized assay, based on the monitoring of uric acid degradation at 300 nm, was confirmed via liquid chromatography. Finally, a panel of 319 QPS (Qualified Presumption of Safety) strains of lactobacilli (18 species covering 9 genera), Bacillus (3 species), and Bifidobacterium (4 species) were screened for uricase activity using the optimized method. All 319 strains, but the positive control Bacillus sp. DSM 1306, were uricase-negative, indicating that this activity is rare among these genera, especially in isolates from food or feces. Altogether, the UV-spectrophotometric high-throughput assay based on whole bacterial suspension reported here can be used to rapidly screen large microbial collection, by simultaneously detecting cell-associated and extracellular uricase activity, thereby accelerating the identification of uricolytic strains with therapeutic potential to treat hyperuricemia.